Medical innovation, education, and labor market outcomes of cancer patients - Sung-hee Jeon; Vincent Pohl (W.E. Upjohn Institute for Employment Research, 2019)
Innovations in cancer treatment have lowered mortality, but little is known about their economic benefits. We assess the effect of two decades of improvements in cancer treatment options on the labor market outcomes of breast and prostate cancer patients. In addition, we compare this effect across cancer patients with different levels of educational attainment. We estimate the effect of medical innovation on cancer patients' labor market outcomes employing tax return and cancer registry data from Canada and measuring medical innovation by using the number of approved drugs and a quality-adjusted patent index. While cancer patients are less likely to work after their diagnosis, we find that the innovations in cancer treatment during the 1990s and 2000s reduced the negative employment effects of cancer by 63-70 percent. These benefits of medical innovation are limited to cancer patients with postsecondary education, raising concerns about unequal access to improved treatment options.
Keywords: I12; I14; I24; I26; J22; O31; 330; medical innovation; breast cancer; prostate cancer; labor supply; employment; earnings; returns to education